Analysis of interpersonal function in greta thunberg speech - Adystianto, Marvelia Pratama; Jayantini, I G A Sri Rwa; Suastini, Ni Wayan (Journal of Language and Applied Linguistics, 2020)
The research aimed to discover the types of interpersonal functions and encourage awareness in a speech. This analysis was conducted using the qualitative method analysis with Greta Thunberg’s speech transcription in the United Nation Climate Action Summit as the subject of analysis. Then, the data were separated into the form of the clauses. The analysis was conducted based on Halliday's theory. The results of analysis showed that declarative sentences dominated Thunberg’s speech, then inclination modality and second personal pronoun “you” predominantly found in the speech. Thunberg also attempted to use the subject “I" and “we” which mediated the speaker and the audience as an effort to communicate their common sense or desires in order to create an "equal" connection. In conclusion, Greta Thunberg aims to address the world leaders regarding climate change issues and even encourage the audience to be proactive in finding a solution to the issue.